FORMATION OF INNOVATIVE HUMAN RESOURCES MANAGEMENT METHODS AS A PROXEOLOGICAL APPROACH (Economic journal of Lesya Ukrainka Volyn National University, 2019)
As you know, one of the main resources and sources of benefits for the enterprise is its personnel, and its proper functioning, in general, is impossible without the influence of management on it, and has become the key to creating a personnel management system. The comprehensive concept of «personnel management» indicates that the process of influencing workers is possible only using special tools and methods. In modern business conditions, radically new, innovative management methods, which also include the praxeological approach, are becoming very relevant. In the traditional methods of personnel management, taking into account the praxeological approach, it is advisable to introduce one more component, «methods for the formation of effective personnel behavior». The purpose of the article is to reveal the essence of a comprehensive definition of personnel management. Formation of innovative methods of personnel management and introduction of their groups into the classification. Defining the classification of technology personnel from the aspect of innovative methods of personnel management. Defining a praxeological approach in personnel management and constructing a schematic representation of the praxeological outline of the concepts of «personnel», «management», «innovation», «method» and «innovative methods of personnel management». Introduced by the author in the classification a group of methods that will allow to carry out a continuous process (planning, hiring, evaluation, development and motivation) influence of the company management on the interests, behavior and activities of employees (who have industrial relations with the employer, skilled or unskilled, may have experience or not to have it at the time of the employment contract), using newly created and / or improved methods of influence in order to achieve the tactical and strategic goals of the enterprise. The complex concept of personnel management is formed. The scheme of praxeological outline of the concepts of «personnel», «management», «innovation», «method» and «innovative methods of personnel management».
Keywords: praxeology, personnel management, personnel management methods, innovations, innovative methods, personnel technologies